Research progress of lignin-derived materials in lithium/sodium ion batteries - Jingke Zhang; Hengxue Xiang; Zhiwei Cao; Shichao Wang; Meifang Zhu (Green Energy & Environment)
With the increase of energy consumption, the shortage of fossil resource, and the aggravation of environmental pollution, the development of cost-effective and environmental friendly bio-based energy storage devices has become an urgent need. As the second most abundant natural polymer found in nature, lignin is mainly produced as the by-product of paper pulping and bio-refining industries. It possesses several inherent advantages, such as low-cost, high carbon content, abundant functional groups, and bio-renewable, making it an attractive candidate for the rechargeable battery material. Consequently, there has been a surge of research interest in utilizing lignin or lignin-based carbon materials as the components of lithium-ion (LIBs) or sodium-ion batteries (SIBs), including the electrode, binder, separator, and electrolyte. This review provides a comprehensive overview on the research progress of lignin-derived materials used in LIBs/SIBs, especially the application of lignin-based carbons as the anodes of LIBs/SIBs. The preparation methods and properties of lignin-derived materials with different dimensions are systemically discussed, which emphasizes on the relationship between the chemical/physical structures of lignin-derived materials and the performances of LIBs/SIBs. The current challenges and future prospects of lignin-derived materials in energy storage devices are also proposed.